Acceptability, engagement, and preliminary efficacy of a college human physiology course with integrated mindfulness practice to support student wellbeing - Zhang, Zhuoya; Lưu, Brother Chân Pháp; Gilbert-Diamond, Diane (Frontiers in Psychology, 2024)
Objective: To evaluate the acceptability of and engagement with an undergraduate human physiology course embedded with mindfulness practice. To assess its preliminary efficacy on student mindfulness and well-being. Methods: Students (N = 36, 17% freshman, 33% sophomore, 22% junior, 28% senior) answered online surveys at course completion. Primary outcomes were course ratings, assignment and assessment completion rates, minutes, types of mindfulness practice, changes in trait mindfulness (Mindful Attention Awareness Scale, MAAS), and self-reported well-being outcomes. We ran Chi-square goodness of fit tests and paired Wilcoxon signed-rank tests to decide if the outcomes differed significantly post-class. We tested the dose-response relation between mindfulness practice time and trait mindfulness and whether the out-of-class practice time was consistent across the weeks with generalized linear mixed-effect models. Results: All participants reported finding the course enjoyable and that they would recommend it to their friends. They practiced for an average of 66 (SD = 27) minutes per week in the class and 112 (SD = 59) minutes on their own. The most common out-of-class practices were mindful movements, sitting meditation, and breathing. Per self-reports, the course increased student understanding of specific mindfulness practices and appreciation for their body. It improved well-being and trait mindfulness (MAAS mean within-person change = 1.2, SD = 0.8, p < .00001). We found no does-response relation between practice time and trait mindfulness. Conclusions: This pilot study supports that incorporating mindfulness practice into college-level courses may promote student well-being and such approaches warrant further investigation.